Sediment ecotoxicity of the insecticide lufenuron to benthic macroinvertebrates - Jollie, Lucas (Student Undergraduate Research E-journal!, 2016)
Pesticides such as lufenuron are widely used in agriculture to preserve crops and maximize harvests. The application of lufenuron might cause it to inadvertently end up in surrounding ecosystems and causing unwanted damage. To assess the potential ecological damage and the fate of lufenuron, sediment toxicity tests using spiked sediment were performed, as well as a sediment aging test. Chironomids appeared as the most sensitive species and the toxicity of lufenuron decreased faster than previously thought at 20°C. Lastly, very little lufenuron can easily cause an environmental risk after application.